Evaluation of Accuracy of Episiotomy Incision in a Governmental Maternity Unit in Palestine: An Observational Study - Hadil Y. Ali-Masri; Sahar J. Hassan; Kaled M. Zimmo; Mohammed W. Zimmo; Khaled M. K. Ismail; Erik Fosse; Hasan Alsalman; Åse Vikanes; Katariina Laine (Obstetrics and Gynecology International)
Episiotomy should be cut at certain internationally set criteria to minimize risk of obstetric anal sphincter injuries (OASIS) and anal incontinence. The aim of this study was to assess the accuracy of cutting right mediolateral episiotomy (RMLE). An institution-based prospective cohort study was undertaken in a Palestinian maternity unit from February 1, to December 31, 2016. Women having vaginal birth at gestational weeks ≥24 or birthweight ≥1000 g and with intended RMLE were eligible (n=240). Transparent plastic films were used to trace sutured episiotomy in relation to the midline within 24-hour postpartum. These were used to measure incisions’ distance from midline, and suture angles were used to classify the incisions into RMLE, lateral, and midline episiotomy groups. Clinical characteristics and association with OASIS were compared between episiotomy groups. A subanalysis by profession (midwife or trainee doctor) was done. Less than 30% were RMLE of which 59% had a suture angle of <40° (equivalent to an incision angle of <60°). There was a trend of higher OASIS rate, but not statistically significant, in the midline (16%, OR: 1.7, CI: 0.61–4.5) and unclassified groups (16.5%, OR: 1.8, CI: 0.8–4.3) than RMLE and lateral groups (10%). No significant differences were observed between episiotomies cut by doctors and midwives. Most of the assessed episiotomies lacked the agreed criteria for RMLE and had less than optimal incision angle which increases risk of severe complications. A well-structured training program on how to cut episiotomy is recommended.